Surface active polymer as well as preparation method and application thereof

By introducing surface-active functional monomers into the macromolecular structure of polyacrylamide, high-molecular-weight surface-active polymers are generated through copolymerization, which solves the problems of poor salt tolerance and chromatographic separation effect in high-temperature and high-salt reservoirs, and achieves good oil displacement effect and improved oil recovery.

CN121495039APending Publication Date: 2026-02-10CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411080880.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Existing high molecular weight partially hydrolyzed polyacrylamide exhibits poor salt tolerance in high-temperature and high-salinity reservoirs, and is prone to hydrolysis and degradation, resulting in poor oil displacement performance. Furthermore, the polymer/surfactant compound system exhibits chromatographic separation effects in the reservoir, impacting oil recovery and economic benefits.

Method used

By introducing surface-active functional monomers into the macromolecular structure of polyacrylamide, high-molecular-weight surface-active polymers are generated through copolymerization. Combining the thickening ability of high molecular weight with the surface activity of low-molecular-weight surfactants, a surface-active polymer with good temperature and salt resistance is formed.

Benefits of technology

It improves the surface activity and temperature and salt resistance of polymers, solves the problem of chromatographic separation effect, enhances oil displacement effect, and improves crude oil recovery rate in tertiary oil recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121495039A_ABST
    Figure CN121495039A_ABST
Patent Text Reader

Abstract

The invention relates to the field of polymer oil-displacing agents, and discloses a surface active polymer as well as a preparation method and application thereof. The surface active polymer comprises a structural unit A as shown in a formula (1), a structural unit B as shown in a formula (2) and a structural unit C as shown in a formula (3), n is an integer of 7-20, and M is an alkali metal element; on the basis of the total weight of the surface active polymer, the content of the structural unit A is 60-89 wt%, the content of the structural unit B is 10-30 wt%, and the content of the structural unit C is 1-30 wt%. The surface active polymer has good surface activity and high-temperature and high-salt resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer flooding agents, and more specifically, to a surface-active polymer, its preparation method, and its application. Background Technology

[0002] High molecular weight partially hydrolyzed polyacrylamide (HMWPA) is a widely used polymer flooding agent in tertiary oil recovery. It exhibits good chemical stability, high viscosity retention, and high swept volume in low-temperature, low-salinity Class I and II reservoirs, thereby improving oil recovery. However, in high-temperature, high-salinity Class III reservoirs, HMWPA exhibits poor salt tolerance, is easily hydrolyzed and severely degraded, and precipitates due to complexation with calcium and magnesium ions, reducing the solution viscosity retention. This diminishes its oil displacement effect in Class III reservoirs, resulting in less economic benefit. Currently, developing oil displacement agents resistant to high-temperature and high-salinity formation conditions for Class III reservoirs (formation temperature 70-95℃, formation salinity 10000-30000 mg / L) has become a research hotspot.

[0003] In tertiary oil recovery technologies, ternary chemical composite flooding can achieve ultra-low interfacial tension between oil and water while maintaining the viscosity of the injected fluid, significantly improving oil recovery. However, the adsorption, diffusion, and migration characteristics of mixtures of different chemical agents in the porous reservoir medium vary considerably, leading to a "chromatographic separation effect" during oil displacement in the reservoir pores. Simultaneously, surfactant loss increases during displacement, reducing recovery and economic benefits. Furthermore, the use of strong alkaline additives results in severe scaling at various stages of the production process, posing challenges to production management.

[0004] To ensure that the oil displacement system maintains sufficiently high viscosity and ultra-low interfacial tension under high salinity and high temperature conditions, it is necessary to break away from the traditional framework of polymer / surfactant composite systems. By combining the thickening ability of polymers with the surface activity of low-molecular-weight surfactants, functional groups with excellent surface activity are introduced into the polymer chain, achieving both thickening and reduced interfacial tension. A single material can function as both a polymer and a surfactant. Therefore, this type of surface-active polymeric oil displacement agent can, to some extent, solve the chromatographic separation effect problem inherent in polymer-surfactant composite flooding. Furthermore, due to the thickening properties of the surface-active functional polymer, it also has a foam-stabilizing effect, acting as a foam stabilizer in foam flooding and multi-element foam composite flooding. These superior properties make it a promising candidate for application in tertiary oil recovery.

[0005] Research on surface-active functional polymers is deepening, and developing new varieties and synthetic methods is currently a research hotspot. However, due to insufficient understanding of the relationship between structure and properties, and the extreme complexity of macromolecular aqueous solutions involving physicochemical properties, research progress in this field of surface-active functional polymers has been slow to date. Therefore, studying the relationship between their structure and properties and synthesizing high-molecular-weight copolymers with good surface activity has significant theoretical and applied value.

[0006] CN1155555A discloses a method for copolymerizing carboxymethyl cellulose, a surface-active macromonomer, and a third monomer to form a terpolymer with high molecular weight and high surface activity, having a molecular weight of 2 × 10⁻⁶. 4 -2×10 5 The surface tension can reach 28-35 mN / m, and the interfacial tension is 0.1-3 mN / m. This copolymer has excellent interfacial activity and effectively overcomes the defect of immiscibility in the application of polymer and low molecular weight surfactant blend solutions, thus reducing costs. However, its molecular weight is relatively low, resulting in low copolymer viscosity, which cannot effectively reduce the oil-water mobility ratio and increase the swept volume to achieve the purpose of improving the recovery rate.

[0007] CN105331347A discloses a method for reacting water-soluble PVA and oil-soluble substances under certain conditions to obtain a modified PVA polyvinyl alcohol polymeric surfactant for oil displacement. The resulting product is both water-soluble and partially oil-soluble, thereby increasing the compatibility of the surfactant solution with crude oil. However, under harsh reservoir conditions, it does not possess the ability to withstand high temperatures and salts, nor the ability to reduce the oil saturation of the affected reservoir.

[0008] Therefore, there is an urgent need for a surface-active polymer that simultaneously possesses good surface activity, good thickening and viscous effects, and good temperature and salt resistance. Summary of the Invention

[0009] The purpose of this invention is to overcome the problem that existing copolymers cannot simultaneously possess good surface activity, good thickening and viscous effects, and good temperature and salt resistance properties, and to provide a surface-active polymer that simultaneously possesses good surface activity, good thickening and viscous effects, and good temperature and salt resistance properties.

[0010] To achieve the above objectives, a first aspect of the present invention provides a surface-active polymer comprising: structural unit A as shown in formula (1), structural unit B as shown in formula (2), and structural unit C as shown in formula (3).

[0011]

[0012] Where n is an integer between 7 and 20, and M is an alkali metal element;

[0013] Based on the total weight of the surface-active polymer, the content of structural unit A is 60-89 wt%, the content of structural unit B is 10-30 wt%, and the content of structural unit C is 1-30 wt%.

[0014] A second aspect of the present invention provides a method for preparing a surface-active polymer, the method comprising: polymerizing a monomer mixture in water in the presence of an initiator, wherein the monomer mixture contains monomer D as shown in formula (4), monomer E as shown in formula (5), and monomer F as shown in formula (6).

[0015]

[0016] Where n is an integer between 7 and 20, and M is an alkali metal element;

[0017] Based on the total weight of the monomer mixture, the amount of monomer D added is 60-89 wt%, the amount of monomer E added is 10-30 wt%, and the amount of monomer F added is 1-30 wt%.

[0018] A third aspect of the present invention provides a surface-active polymer prepared by the preparation method provided by the present invention.

[0019] A fourth aspect of the present invention provides an application of the surface-active polymer provided by the present invention as a polymeric oil displacement agent.

[0020] The beneficial effects of the present invention through the above technical solution are:

[0021] This invention, from a molecular design perspective, introduces surface-active functional monomers E and F into the macromolecular structure of polyacrylamide. This provides surface activity to the polymer and improves the polymer's temperature and salt resistance. In a preferred embodiment, adding molecular weight regulators to the polymerization system not only adjusts the polymer's molecular weight but also increases the polymerization activity of the carbon-carbon double bonds in the molecular structures of monomers E and F, allowing them to copolymerize with acrylamide and various other olefin monomers to form different functional polymers. The polyether structure in monomer E provides excellent hydrophilicity and surface activity, while also exhibiting resistance to acids and hard water. The phosphate monoester structure in monomer F provides excellent hydrophilicity and surface activity. The surface-active functional polymer described in this invention combines the thickening properties of high molecular weight polymers with the surface activity of low molecular weight surfactants, offering advantages such as easy flow control and reduced oil / water interfacial tension. It possesses the dual functions of viscoelastic oil displacement and active oil washing, and can replace currently used polymer / surfactant binary composite flooding systems in oilfields, solving problems such as chromatographic separation effects in formations associated with binary composite flooding. The surface-active functional polymers of this invention can effectively solve the problems of poor temperature resistance and resistance to inorganic high-valence cations in existing oil displacement systems, exhibiting excellent surface activity. Therefore, this type of polymer oil displacement agent is suitable for high-temperature, high-salinity Class III oil reservoirs and can further improve crude oil recovery in tertiary oil recovery.

[0022] Furthermore, in a preferred embodiment of the present invention, by selecting appropriate monomer ratios, polymerization conditions, and suitable types and contents of initiators, auxiliaries, and molecular weight regulators, the apparent viscosity, surface tension reduction ability, and temperature and salt resistance of the surface-active polymer are further improved. The viscosity-average molecular weight of the obtained polymers can reach over 11 million g / mol. When prepared into a 1500 mg / L aqueous solution using brine with a mineralization of 15 g / L, the polymer is subjected to a shear rate of 7.34 s⁻¹. -1 At 25℃, its apparent viscosity can reach 38.8-59 mPa·s, and when the temperature is raised to 80℃, the apparent viscosity is still 15.1-26.6 mPa·s. When prepared into a 1500 mg / L aqueous solution using brine with a mineralization of 25 g / L, at a shear rate of 7.34 s⁻¹... -1 At a temperature of 25℃, its apparent viscosity can reach 20.2-38.5 mPa·s, and when the temperature is raised to 80℃, the viscosity is still 11.6-18.7 mPa·s. Meanwhile, the surface tension of the polymer aqueous solution with a concentration of 1500 mg / L is between 31.5 mN / m and 35.6 mN / m. Detailed Implementation

[0023] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0024] The first aspect of the present invention provides a surface-active polymer, the surface-active polymer comprising: structural unit A shown in formula (1), structural unit B shown in formula (2), and structural unit C shown in formula (3).

[0025]

[0026] Where n is an integer from 7 to 20, and M is an alkali metal element, such as K or Na; preferably, in formula (2), -C m H 2m+1 It is a straight-chain alkyl group;

[0027] Based on the total weight of the temperature-resistant and salt-resistant surfactant polymer, the content of structural unit A is 60-89 wt%, the content of structural unit B is 10-30 wt%, and the content of structural unit C is 1-30 wt%.

[0028] Furthermore, based on the weight of the surface-active polymer, the content of structural unit A is 70-89 wt%, the content of structural unit B is 10-20 wt%, and the content of structural unit C is 1-10 wt%.

[0029] According to the present invention, preferably, n is 7, 9 or 15; m is an integer from 10 to 14, preferably 12.

[0030] According to the present invention, preferably, p is an integer from 6 to 10, and more preferably 8.

[0031] In a preferred embodiment of the present invention, the structural unit B is selected from at least one of the structural units shown in formula (7), formula (8), and formula (9), and / or the structural unit C is selected from the structural unit shown in formula (13).

[0032]

[0033] The inventors of this invention discovered in their research that when structural unit A is the structural unit shown in formula (1), structural unit B is selected from at least one of the structural units shown in formula (7), formula (8), and formula (9), and structural unit C is the structural unit shown in formula (13), the polymer composed of specific structural units A, B, and C can achieve better oil displacement effect when used as an oil displacement agent.

[0034] According to the present invention, preferably, the surface-active polymer is selected from one of the following polymers:

[0035] Polymer-1: comprising the structural unit shown in formula (1), the structural unit shown in formula (7), and the structural unit shown in formula (13).

[0036] Polymer-2: comprises the structural unit shown in formula (1), the structural unit shown in formula (8), and the structural unit shown in formula (13).

[0037] Polymer-3: contains the structural unit shown in formula (1), the structural unit shown in formula (9) and the structural unit shown in formula (13).

[0038] According to the present invention, preferably, the viscosity-average molecular weight of the surface-active polymer is 10 million g / mol to 15 million g / mol.

[0039] Furthermore, the viscosity-average molecular weight of the surface-active polymer is 11 million g / mol to 15 million g / mol.

[0040] According to the present invention, preferably, the intrinsic viscosity η of the surfactant is 1900-2600 mL / g, and / or, the surface tension of a solution of the surfactant at a concentration of 1500 mg / L is 31-40 mN / m at 25°C.

[0041] Furthermore, the intrinsic viscosity η of the surfactant polymer is 2050-2600 mL / g, and / or the surface tension of a solution of the surfactant polymer at a concentration of 1500 mg / L is 31.5-35.6 mN / m at 25°C.

[0042] A second aspect of the present invention provides a method for preparing a surface-active polymer, the method comprising: polymerizing a monomer mixture in water in the presence of an initiator, wherein the monomer mixture contains monomer D as shown in formula (4), monomer E as shown in formula (5), and monomer F as shown in formula (6).

[0043]

[0044] Where n is an integer from 7 to 20, and M is an alkali metal element; preferably, in formula (5), -Cm H 2m+1 It is a straight-chain alkyl group;

[0045] Based on the total weight of the monomer mixture, the amount of monomer D added is 60-89 wt%, the amount of monomer E added is 10-30 wt%, and the amount of monomer F added is 1-30 wt%.

[0046] Furthermore, based on the total weight of the monomer mixture, the amount of structural monomer D added is 70-89 wt%, the amount of monomer E added is 10-20 wt%, and the amount of monomer F added is 1-10 wt%.

[0047] According to the present invention, preferably, n is 7, 9 or 15; m is an integer from 10 to 14, preferably 12.

[0048] According to the present invention, preferably, p is an integer from 6 to 10, and more preferably 8.

[0049] In a preferred embodiment of the present invention, the monomer E is selected from at least one of the monomers shown in formula (10), formula (11), and formula (12), and / or the monomer F is selected from the monomer shown in formula (14).

[0050]

[0051] Preferably, the amount of monomer mixture added is 15-35 wt%, based on the total weight of water and the monomer mixture.

[0052] Furthermore, based on the total weight of water and the monomer mixture, the amount of monomer mixture added is 20-30 wt%.

[0053] The inventors of this invention discovered in their research that when monomer D is the monomer shown in formula (4), monomer E is selected from at least one of the monomers shown in formula (10), formula (11), and formula (12), and monomer F is the monomer shown in formula (14), the polymer obtained by reacting specific monomers D, E, and F can achieve a better oil displacement effect when used as an oil displacement agent.

[0054] According to the present invention, preferably, the polymerization reaction is carried out at a temperature of 0-25°C for a time of 2-15 hours.

[0055] Furthermore, the polymerization reaction is carried out at a temperature of 0-15°C for a time of 10-15 hours.

[0056] According to the present invention, preferably, the polymerization reaction is carried out under conditions of pH 7-10.

[0057] Furthermore, the polymerization reaction is carried out under conditions of pH 7-9.

[0058] In this invention, the above-mentioned pH value can be obtained by adding a pH adjuster to the polymerization system. The pH adjuster used to adjust the pH value can be any of the pH adjusters commonly used in the art, such as at least one of sodium hydroxide, sodium carbonate, potassium carbonate and ammonia water.

[0059] Preferably, the pH adjuster is sodium hydroxide.

[0060] According to the present invention, preferably, the polymerization reaction is carried out in the presence of a protective gas, which is a gas that does not react with the raw materials and products, and can be at least one of nitrogen gas and group 0 element gases in the periodic table, which are conventional in the art.

[0061] According to the present invention, preferably, the protective gas is selected from nitrogen and / or argon.

[0062] In this invention, the amount of the initiator is not particularly limited and can vary within a wide range. According to this invention, preferably, the amount of the initiator added is 0.01-0.1 wt%, based on the total weight of the monomer mixture.

[0063] In this invention, the initiator can be any of the various free radical initiators commonly used in the art. The free radical initiator can be an azo initiator, a peroxide initiator, or a redox initiator. Specifically, the azo initiator can be selected from any one or more of dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride, azodicarbonamide, azobisisopropylimidazoline hydrochloride, azoisobutylcyanoformamide, azodicyclohexylformonitrile, azodicyanvalerate, azobisisopropylimidazoline, azobisisobutyronitrile, azobisisovalerate, and azobisisoheptanenitrile; the peroxide initiator can be selected from any one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, benzoyl peroxide, and benzoyl tert-butyl peroxide; the redox initiator can be selected from any one or more of sulfate-sulfite, persulfate-thiourea, persulfate-organic salt, and ammonium persulfate-aliphatic amine.

[0064] According to the present invention, preferably, the polymerization reaction is carried out in the presence of a chelating agent. The addition of a chelating agent can prevent the influence of metal ions on the polymerization reaction.

[0065] According to the present invention, preferably, the amount of chelating agent added is 0.1-0.3 wt%, based on the total weight of the monomer mixture.

[0066] According to the present invention, preferably, the chelating agent is selected from at least one of disodium ethylenediaminetetraacetate, aminotriacetic acid and ammonium citrate, and more preferably disodium ethylenediaminetetraacetate.

[0067] According to the present invention, preferably, the polymerization reaction is carried out in the presence of an auxiliary agent. The addition of the auxiliary agent can improve the solubility of the copolymer.

[0068] According to the present invention, preferably, the amount of the additive added is 0.01-0.1 wt%, based on the total weight of the monomer mixture;

[0069] According to the present invention, preferably, the adjuvant is selected from at least one of urea, thiourea and ammonia water, and preferably urea.

[0070] According to the present invention, preferably, the polymerization reaction is carried out in the presence of a molecular weight regulator. Adding a molecular weight regulator to the polymerization system can not only adjust the polymer molecular weight, but also increase the polymerization activity of the carbon-carbon double bonds in the molecular structures of monomers E and F, enabling them to copolymerize with acrylamide to form different functional polymers.

[0071] According to the present invention, preferably, the amount of the molecular weight regulator added is 0.02-0.1 wt%, based on the total weight of the monomer mixture.

[0072] According to the present invention, preferably, the molecular weight regulator is selected from at least one of isopropanol, ammonia, N,N'-methylenebisacrylamide and dimethylthiourea, and more preferably a mixture of isopropanol and ammonia.

[0073] According to the present invention, preferably, the weight ratio of isopropanol to ammonia in the molecular weight regulator is (15-35):1.

[0074] According to the present invention, preferably, the method for preparing the surface-active polymer further includes purifying and drying the mixture obtained after the polymerization reaction to obtain a purified polymer. The purification is preferably performed using acetone to precipitate and purify the mixture.

[0075] A third aspect of the present invention provides a surface-active polymer prepared by the preparation method provided by the present invention.

[0076] A fourth aspect of this invention provides an application of the surfactant polymer provided by this invention as a polymer flooding agent. The surfactant polymer can be used as a polymer flooding agent and is suitable for high-temperature (80-90℃) and high-salinity (mineralization 5-25 g / L) oil reservoirs, further improving crude oil recovery in tertiary oil recovery processes.

[0077] The present invention will be described in detail below through embodiments. The test methods involved in the following embodiments are as follows:

[0078] The dissolution time and solid content of the polymer were determined according to the method specified in GB12005.8-89.

[0079] The intrinsic viscosity η of the polymer was determined according to the method for determining the intrinsic viscosity of polyacrylamide specified in GB12005.1-89, using an Ubbelohde viscometer at 25°C for a 10% by weight NaCl solution.

[0080] The viscosity-average molecular weight is calculated using the formula M = (η / K). 1 / α The calculation yields K = 4.5 × 10⁻⁶. -3 , α=0.80.

[0081] The apparent viscosity of the polymer solution was measured using a Brookfield DV-III viscometer at a constant shear rate of 7.34 s⁻¹. -1 .

[0082] Surface tension was measured using a Dataphysics DCAT21 surface tension meter.

[0083] Molecular structural formulas and the composition of structural units are quantitatively analyzed. 13 C-NMR spectroscopy determination.

[0084] All reagents used in the examples and comparative examples were commercially available chemically pure reagents. The polymer sample KYP was an in-use sample provided by the oil field. KYP contains acrylamide structural units and 2-methyl-2-acrylamidopropanesulfonic acid structural units. Based on the weight of KYP, the content of acrylamide structural units was 75% by weight, and the content of 2-methyl-2-acrylamidopropanesulfonic acid structural units was 25% by weight. The viscosity-average molecular weight of KYP was 10.1 million g / mol, and the intrinsic viscosity was 1915 mL / g.

[0085] Example 1

[0086] An aqueous solution polymerization method was used. 266.25 g of acrylamide, 71.25 g of dodecyl alcohol polyoxyethylene ether methacrylate as shown in formula (10), 37.5 g of phosphate monoester surfactant monomer as shown in formula (14) (prepared according to the method in Applied Chemistry, 2005, (7): 804-807), and distilled water were added to the polymerization reaction flask. The total monomer content was 25% by weight, based on the total content of monomer and distilled water. The mixture was stirred thoroughly until the solution in the polymerization reaction flask became a transparent solution. Then, 120 mg of urea, 375 mg of disodium ethylenediaminetetraacetate, 5 mL of ammonia water, and 150 mg of isopropanol were added. Simultaneously, the pH of the system was adjusted to 9 with sodium hydroxide, and the initial temperature of the system was controlled at 15°C. High-purity nitrogen gas with a volume concentration of 99.99% was introduced for 30 minutes to remove oxygen from the polymerization reaction flask. Then, 100 mg of ammonium persulfate and 50 mg of sodium bisulfite were added sequentially, and high-purity nitrogen gas was continuously introduced for 10 minutes. The reactor was then sealed and reacted for 10 hours to obtain a transparent and viscous polymer. The gel-like product was removed, and after granulation, drying, crushing, and sieving, a high molecular weight, temperature-resistant and salt-resistant surfactant polymer product P1 was obtained.

[0087] Performance determination of polymer P1: Quantitative analysis 13 The C-NMR spectra showed C=O, COC, and -CH2-PO3 in equation (15) at 176.22 ppm, 72.16 ppm, and 59.53 ppm, respectively. - The characteristic peaks of the bond, along with the superposition of the characteristic peaks of -CH-CH2- and C=O on the main chain, confirm that the obtained copolymer molecule has the structure shown in formula (15). The x1:y1:z1 ratio can be calculated to be 1:0.034:0.025 by the integral area of ​​the characteristic peaks. The intrinsic viscosity of polymer P1 is 2079 mL / g, and the viscosity-average molecular weight is 11.26 million g / mol.

[0088]

[0089] Example 2

[0090] An aqueous solution polymerization method was used. 285g of acrylamide, 56.25g of dodecyl alcohol polyoxyethylene ether methacrylate as shown in formula (10), 33.75g of phosphate monoester surfactant monomer as shown in formula (14) (prepared according to the method in Applied Chemistry, 2005, (7): 804-807), and distilled water were added to the polymerization reaction flask. The total monomer content was 25% by weight, based on the total content of monomer and distilled water. The mixture was stirred thoroughly until the solution in the polymerization reaction flask became a transparent solution. Then, 120mg of urea, 400mg of disodium ethylenediaminetetraacetate, 5mL of ammonia water, and 120mg of isopropanol were added. Simultaneously, the pH of the system was adjusted to 8 with sodium hydroxide, and the initial temperature of the system was controlled at 10°C. High-purity nitrogen gas with a volume concentration of 99.99% was introduced for 30 minutes to remove oxygen from the polymerization reaction flask. Then, 60 mg of ammonium persulfate and 30 mg of sodium bisulfite were added sequentially, and high-purity nitrogen gas was continuously introduced for 10 minutes. The reactor was then sealed and reacted for 12 hours to obtain a transparent and viscous polymer. The gel-like product was removed, and after granulation, drying, pulverization, and sieving, a high molecular weight, temperature-resistant and salt-resistant surfactant polymer product P2 was obtained.

[0091] Performance determination of polymer P2: Quantitative analysis 13 The C-NMR spectra showed C=O, COC, and -CH2-PO3 in equation (15) at 176.22 ppm, 72.16 ppm, and 59.53 ppm, respectively. - The characteristic peaks of the bond, along with the superposition of the characteristic peaks of -CH-CH2- and C=O on the main chain, indicate that the obtained copolymer molecule has the structure shown in formula (15). The x1:y1:z1 ratio can be calculated as 1:0.025:0.021 by the integral area of ​​the characteristic peaks. The intrinsic viscosity of polymer P2 is 2216 mL / g, and the viscosity-average molecular weight is 12.19 million g / mol.

[0092] Example 3

[0093] An aqueous solution polymerization method was used. 296.25 g of acrylamide, 52.5 g of dodecyl alcohol polyoxyethylene ether methacrylate as shown in formula (11), 26.25 g of phosphate monoester surfactant monomer as shown in formula (14) (prepared according to the method in Applied Chemistry, 2005, (7): 804-807), and distilled water were added to the polymerization reaction flask. The total monomer content was 25% by weight, based on the total content of monomer and distilled water. The mixture was stirred thoroughly until the solution in the polymerization reaction flask became a transparent solution. Then, 100 mg of urea, 500 mg of disodium ethylenediaminetetraacetate, 10 mL of ammonia water, and 150 mg of isopropanol were added. Simultaneously, the pH of the system was adjusted to 7 with sodium hydroxide, and the initial temperature of the system was controlled at 8°C. High-purity nitrogen gas with a volume concentration of 99.99% was introduced for 30 minutes to remove oxygen from the polymerization reaction flask. Then, 60 mg of ammonium persulfate and 30 mg of sodium bisulfite were added sequentially, and high-purity nitrogen gas was continuously introduced for 10 minutes. The reactor was then sealed and reacted for 12 hours to obtain a transparent and viscous polymer. The gel-like product was removed, and after granulation, drying, crushing, and sieving, a high molecular weight, temperature-resistant and salt-resistant surfactant polymer product P3 was obtained.

[0094] Performance determination of polymer P3: quantitative analysis 13 The C-NMR spectra showed C=O, COC, and -CH2-PO3 in equation (16) at 176.22 ppm, 72.16 ppm, and 59.53 ppm, respectively. - The characteristic peaks of the bond, along with the superposition of the characteristic peaks of -CH-CH2- and C=O on the main chain, confirm that the obtained copolymer molecule has the structure shown in formula (16). The x1:y1:z1 ratio can be calculated to be 1:0.019:0.016 by the integral area of ​​the characteristic peaks. The intrinsic viscosity of polymer P3 is 2311 mL / g, and the viscosity-average molecular weight is 12.85 million g / mol.

[0095]

[0096] Example 4

[0097] An aqueous solution polymerization method was used. 300g of acrylamide, 54.375g of dodecyl alcohol polyoxyethylene ether methacrylate as shown in formula (11), 20.625g of phosphate monoester surfactant monomer as shown in formula (14) (prepared according to the method in Applied Chemistry, 2005, (7): 804-807), and distilled water were added to the polymerization reaction flask. The total monomer content was 25% by weight, based on the total content of monomer and distilled water. The mixture was stirred thoroughly until the solution in the polymerization reaction flask became a transparent solution. Then, 150mg of urea, 800mg of disodium ethylenediaminetetraacetate, 5mL of ammonia water, and 150mg of isopropanol were added. Simultaneously, the pH of the system was adjusted to 8 with sodium hydroxide, and the initial temperature of the system was controlled at 5°C. High-purity nitrogen gas with a volume concentration of 99.99% was introduced for 30 minutes to remove oxygen from the polymerization reaction flask. Then, 60 mg of ammonium persulfate and 30 mg of sodium bisulfite were added sequentially, and high-purity nitrogen gas was continuously introduced for 10 minutes. The reactor was then sealed and reacted for 12 hours to obtain a transparent and viscous polymer. The gel-like product was removed, and after granulation, drying, pulverization, and sieving, a high molecular weight, temperature-resistant and salt-resistant surfactant polymer product P4 was obtained.

[0098] Performance determination of polymer P4: Quantitative analysis 13 The C-NMR spectra showed C=O, COC, and -CH2-PO3 in equation (16) at 176.22 ppm, 72.16 ppm, and 59.53 ppm, respectively. - The characteristic peaks of the bond, along with the superposition of the characteristic peaks of -CH-CH2- and C=O on the main chain, confirm that the obtained copolymer molecule has the structure shown in formula (16). The x1:y1:z1 ratio can be calculated as 1:0.020:0.012 by the integral area of ​​the characteristic peaks. The intrinsic viscosity of polymer P4 is 2400 mL / g, and the viscosity-average molecular weight is 13.47 million g / mol.

[0099] Example 5

[0100] An aqueous solution polymerization method was used. 307.5 g of acrylamide, 63.75 g of dodecyl alcohol polyoxyethylene ether methacrylate as shown in formula (12), 11.25 g of phosphate monoester surfactant monomer as shown in formula (14) (prepared according to the method in Applied Chemistry, 2005, (7): 804-807), and distilled water were added to the polymerization reaction flask. The total monomer content was 25% by weight, based on the total content of monomer and distilled water. The mixture was stirred thoroughly until the solution in the polymerization reaction flask became a transparent solution. Then, 120 mg of urea, 600 mg of disodium ethylenediaminetetraacetate, 5 mL of ammonia water, and 150 mg of isopropanol were added. Simultaneously, the pH of the system was adjusted to 7 with sodium hydroxide, and the initial temperature of the system was controlled at 0°C. High-purity nitrogen gas with a volume concentration of 99.99% was introduced for 30 minutes to remove oxygen from the polymerization reaction flask. Then, 100 mg of ammonium persulfate and 50 mg of sodium bisulfite were added sequentially, and high-purity nitrogen gas was continuously introduced for 10 minutes. The reactor was then sealed and reacted for 15 hours to obtain a transparent and viscous polymer. The gel-like product was removed, and after granulation, drying, crushing, and sieving, a high molecular weight, temperature-resistant and salt-resistant surfactant polymer product P5 was obtained.

[0101] Performance determination of polymer P5: Quantitative analysis 13 The C-NMR spectra showed C=O, COC, and -CH2-PO3 in equation (17) at 176.22 ppm, 72.16 ppm, and 59.53 ppm, respectively. - The characteristic peaks of the bond, along with the superposition of the characteristic peaks of -CH-CH2- and C=O on the main chain, indicate that the obtained copolymer molecule has the structure shown in formula (17). The x1:y1:z1 ratio can be calculated to be 1:0.016:0.007 by the integral area of ​​the characteristic peaks. The intrinsic viscosity of polymer P5 is 2515 mL / g, and the viscosity-average molecular weight is 14.28 million g / mol.

[0102]

[0103] Example 6

[0104] An aqueous solution polymerization method was used. 318.75 g of acrylamide, 39.375 g of dodecyl alcohol polyoxyethylene ether methacrylate as shown in formula (12), 16.875 g of phosphate monoester surfactant monomer with the structure shown in formula (14) (prepared according to the method in Applied Chemistry, 2005, (7): 804-807), and distilled water were added to the polymerization reaction flask. The total monomer content was 25% by weight, based on the total content of monomer and distilled water. The mixture was stirred thoroughly until the solution in the polymerization reaction flask became a transparent solution. Then, 120 mg of urea, 480 mg of disodium ethylenediaminetetraacetate, 5 mL of ammonia water, and 150 mg of isopropanol were added. Simultaneously, the pH of the system was adjusted to 8 with sodium hydroxide, and the initial temperature of the system was controlled at 0°C. High-purity nitrogen gas with a volume concentration of 99.99% was introduced for 30 minutes to remove oxygen from the polymerization reaction flask. Then, 60 mg of ammonium persulfate and 30 mg of sodium bisulfite were added sequentially, and high-purity nitrogen gas was continuously introduced for 10 minutes. The reactor was then sealed and reacted for 15 hours to obtain a transparent and viscous polymer. The gel-like product was removed, and after granulation, drying, pulverization, and sieving, a high molecular weight, temperature-resistant and salt-resistant surfactant polymer product P6 was obtained.

[0105] Performance determination of polymer P6: quantitative analysis 13 The C-NMR spectra showed C=O, COC, and -CH2-PO3 in equation (17) at 176.22 ppm, 72.16 ppm, and 59.53 ppm, respectively. - The characteristic peaks of the bond, along with the superposition of the characteristic peaks of -CH-CH2- and C=O on the main chain, confirm that the obtained copolymer molecule has the structure shown in formula (17). The x1:y1:z1 ratio can be calculated as 1:0.010:0.009 by the integral area of ​​the characteristic peaks. The intrinsic viscosity of polymer P6 is 2600 mL / g, and the viscosity-average molecular weight is 14.89 million g / mol.

[0106] Example 7

[0107] The temperature- and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that the weight ratio of each monomer was different. Specifically, the amount of acrylamide added was 225g, the amount of n-dodecyl alcohol polyoxyethylene ether methacrylate shown in formula (10) was 112.5g, and the amount of phosphate monoester surfactant monomer shown in formula (14) was 37.5g. The temperature- and salt-resistant surfactant polymer product P7 was obtained.

[0108] Performance determination of polymer P7: quantitative analysis 13The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1. The x1:y1:z1 ratio can be calculated to be 1:0.063:0.03 based on the integrated area of ​​the characteristic peaks. The intrinsic viscosity of polymer P7 is 1902 mL / g, and the viscosity-average molecular weight is 10.07 million g / mol.

[0109] Example 8

[0110] The temperature-resistant and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that the dodecyl alcohol polyoxyethylene ether methacrylate shown in formula (10) was replaced with an equal weight of the same amount. The dodecyl alcohol polyoxyethylene ether methacrylate shown is obtained. Temperature- and salt-resistant surfactant polymer product P8 is obtained.

[0111] Performance determination of polymer P8: quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 3. The x1:y1:z1 ratio can be calculated as 1:0.029:0.025 based on the integrated area of ​​the characteristic peaks. The intrinsic viscosity of polymer P8 is 1993 mL / g, and the viscosity-average molecular weight is 10.68 million g / mol.

[0112] Example 9

[0113] The temperature- and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that the proportion of monomer in distilled water was different. Specifically, based on the total content of monomer and distilled water, the total content of monomer was 15 wt%. The temperature- and salt-resistant surfactant polymer product P9 was obtained.

[0114] Performance determination of polymer P9: Quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1, and the integrated area ratio of the characteristic peaks is also the same as in Example 1. The intrinsic viscosity of polymer P9 is 1972 mL / g, and the viscosity-average molecular weight is 10.54 million g / mol.

[0115] Example 10

[0116] The temperature- and salt-resistant surfactant polymer product was prepared according to the method in Example 1, except that the polymerization temperature and time were different. Specifically, the initial temperature of the system was controlled at 20°C, high-purity nitrogen was introduced for 10 minutes, the reactor was sealed, and the reaction was carried out for 8 hours. The temperature- and salt-resistant surfactant polymer product P10 was obtained.

[0117] Performance determination of polymer P10: Quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1, and the integrated area ratio of the characteristic peaks is also the same as in Example 1. The intrinsic viscosity of polymer P10 is 1950 mL / g, and the viscosity-average molecular weight is 10.35 million g / mol.

[0118] Example 11

[0119] The temperature- and salt-resistant surfactant polymer product was prepared according to the method in Example 1, except that the amount of initiator added was different. Specifically, the amount of ammonium persulfate added was 300 mg, and the amount of sodium bisulfite added was 150 mg. The temperature- and salt-resistant surfactant polymer product P11 was obtained.

[0120] Performance determination of polymer P11: Quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1, and the integrated area ratio of the characteristic peaks is also the same as in Example 1. The intrinsic viscosity of polymer P11 is 1927 mL / g, and the viscosity-average molecular weight is 10.24 million g / mol.

[0121] Example 12

[0122] A temperature- and salt-resistant surfactant polymer product was prepared according to the method in Example 1, except that the type of chelating agent was different. Specifically, aminotriacetic acid was used to replace an equal weight of disodium ethylenediaminetetraacetate. The temperature- and salt-resistant surfactant polymer product P12 was obtained.

[0123] Performance determination of polymer P12: Quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1, and the integrated area ratio of the characteristic peaks is also the same as in Example 1. The intrinsic viscosity of polymer P12 is 1976 mL / g, and the viscosity-average molecular weight is 10.56 million g / mol.

[0124] Example 13

[0125] A temperature- and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that the type of additive was different. Specifically, thiourea was used to replace an equal weight of urea. The resulting temperature- and salt-resistant surfactant polymer product P13 was obtained.

[0126] Performance determination of polymer P13: quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1, and the integrated area ratio of the characteristic peaks is also the same as in Example 1. The intrinsic viscosity of polymer P13 is 2032 mL / g, and the viscosity-average molecular weight is 10.94 million g / mol.

[0127] Example 14

[0128] A temperature- and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that the type of molecular weight regulator was different. Specifically, dimethylthiourea was used to replace an equal weight of isopropanol. The resulting temperature- and salt-resistant surfactant polymer product P14 was obtained.

[0129] Performance determination of polymer P14: Quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1, and the integrated area ratio of the characteristic peaks is also the same as in Example 1. The intrinsic viscosity of polymer P14 is 1992 mL / g, and the viscosity-average molecular weight is 10.67 million g / mol.

[0130] Example 15

[0131] A temperature- and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that the type of phosphate monoester surfactant monomer was different. Specifically, the phosphate monoester surfactant monomer had a p=6 and M=Na. The temperature- and salt-resistant surfactant polymer product P15 was obtained.

[0132] Performance determination of polymer P15: Quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1. The x1:y1:z1 ratio can be calculated to be 1:0.034:0.028 based on the integrated area of ​​the characteristic peaks. The intrinsic viscosity of polymer P15 is 2038 mL / g, and the viscosity-average molecular weight is 10.98 million g / mol.

[0133] Comparative Example 1

[0134] The temperature-resistant and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that the weight ratio of each monomer was different. Specifically, the amount of acrylamide added was 187.5 g, the amount of n-dodecyl alcohol polyoxyethylene ether methacrylate shown in formula (10) was 37.5 g, and the amount of phosphate monoester surfactant monomer shown in formula (6) was 150 g. Polymer product D1 was obtained.

[0135] Performance determination of polymers: quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1. The x1:y1:z1 ratio can be calculated as 1:0.025:0.143 based on the integrated area of ​​the characteristic peaks. The intrinsic viscosity of polymer D1 is 1414 mL / g, and the viscosity-average molecular weight is 6.95 million g / mol.

[0136] Comparative Example 2

[0137] A temperature- and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that acrylic acid was used instead of an equal weight of acrylamide. Polymer product D2 was obtained.

[0138] Performance determination of polymers: quantitative analysis 13The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1. The x1:y1:z1 ratio can be calculated as 1:0.034:0.025 based on the integrated area of ​​the characteristic peaks. The intrinsic viscosity of polymer D2 is 1662 mL / g, and the viscosity-average molecular weight is 8.51 million g / mol.

[0139] Comparative Example 3

[0140] A temperature- and salt-resistant surfactant polymer product was prepared according to the method of Example 1, except that the number of polyoxyethylene groups in the n-dodecyl alcohol polyoxyethylene ether methacrylate was 2 (n=2). Polymer product D3 was obtained.

[0141] Performance determination of polymers: quantitative analysis 13 The positions of the characteristic peaks in the C-NMR spectrum are approximately the same as in Example 1. The x1:y1:z1 ratio can be calculated as 1:0.056:0.025 based on the integrated area of ​​the characteristic peaks. The intrinsic viscosity of polymer D3 is 1326 mL / g, and the viscosity-average molecular weight is 6.42 million g / mol.

[0142] Test Example 1

[0143] Polymer solutions were prepared using simulated formation water with oilfield salinity of 5 g / L, 15 g / L, and 25 g / L, respectively, along with an acrylamide polymer (code-named KYP) provided by the oilfield. The polymer solutions were then subjected to a shear rate of 7.34 s⁻¹. -1 Table 1 shows the apparent viscosities of the temperature- and salt-resistant surfactant polymer solutions formulated from the polymers obtained in the various embodiments and comparative examples, and the polymer solution formulated from the acrylamide polymer designated KYP, at different temperatures and salinities. Here, salinity refers to the Na+ content in simulated formation water. + K + Ca 2+ Mg 2+ Cl - SO4 2- CO3 2- The sum of the contents of inorganic ions, etc.

[0144] Table 1

[0145]

[0146]

[0147] As shown in Table 1, the polymer aqueous solutions prepared in Examples 1-14 exhibit a high apparent viscosity at 25°C. When the temperature rises to 80°C and the mineralization is 15 g / L, the apparent viscosity of the polymer aqueous solution reaches 12.1-26.6 mPa·s. Even at a mineralization of 25 g / L, the apparent viscosity remains high, and at 80°C, the apparent viscosity still reaches 8.8-18.7 mPa·s. The acrylamide polymer aqueous solution (code-named KYP) provided by the oilfield has a high apparent viscosity at 25°C and a mineralization of 5 g / L, but the apparent viscosity decreases significantly with increasing temperature and mineralization. Comparative Example 1 changed the weight ratio of each monomer, and Comparative Example 2 replaced an equal weight of acrylamide with acrylic acid. Compared with Examples 1-14, the apparent viscosity of the polymer aqueous solutions prepared in Comparative Examples 1-2 decreased significantly at temperatures of 25°C and 80°C, and mineralizations of 5 g / L, 15 g / L, and 25 g / L. This demonstrates that the surface-active polymer of the present invention has good temperature and salt resistance.

[0148] Furthermore, Example 7 changed the weight ratio of each monomer, Example 8 changed the n value in monomer E, Example 9 changed the proportion of monomer in distilled water, Example 10 changed the polymerization reaction conditions, Example 11 changed the amount of initiator added, Examples 12-14 changed the types of chelating agents, auxiliaries, and molecular weight regulators, respectively, and Example 15 changed the p value and the type of alkali metal element in monomer F. Compared with the polymer aqueous solution prepared in Example 1, the apparent viscosity of the polymer aqueous solution prepared in Examples 7-15 was reduced at the same temperature and the same degree of salinity. This shows that when the types of each monomer, the weight ratio of each monomer, the proportion of monomer in distilled water, the polymerization reaction conditions, and the types and amounts of initiators, chelating agents, auxiliaries, and molecular weight regulators meet the preferred conditions, the temperature and salt resistance properties of the surface-active polymer can be further improved.

[0149] Test Example 2

[0150] The performance of the temperature-resistant and salt-resistant surfactants prepared in the various examples and comparative examples was compared with that of the acrylamide polymer KYP provided by the oilfield. The surface tension of polymer aqueous solutions of different concentrations prepared with simulated formation water with a salinity of 15 g / L at 25 °C was measured, and the results are shown in Table 2.

[0151] Table 2

[0152] 100mg / L 500mg / L 1000mg / L 1500mg / L 2000mg / L 2500mg / L Example 1 63.3 55 43.3 31.5 31.2 31.3 Example 2 63.5 54.2 44 32.7 32.2 32.5 Example 3 64 54.1 43.9 33.3 32.8 33 Example 4 64.8 54.9 46.1 34.8 33 33.2 Example 5 64.5 55.1 45 34 33.3 33.1 Example 6 64.9 56.8 45.3 35.6 34.6 34.3 Example 7 63.5 55.3 43.5 31.7 31.4 31.4 Example 8 65.9 57.7 45.6 35.8 34.4 34.4 Example 9 65.7 56.8 44.9 32.7 32.3 32.1 Example 10 65.6 56.4 44.3 32.2 31.9 31.8 Example 11 65.4 55.9 43.9 31.8 31.6 31.7 Example 12 63.9 55.6 43.7 31.8 31.8 31.8 Example 13 63.9 55.8 43.7 31.9 31.9 31.8 Example 14 64 55.8 43.9 32 31.9 31.9 Example 15 64.2 55.9 43.8 32.2 32.3 32 KYP 68.9 67.3 65.1 62.9 63.1 63.3 Comparative Example 1 67.2 63.4 58.2 55.3 52.4 51.6 Comparative Example 2 63.5 55.5 44.2 33.1 32.2 32.2 Comparative Example 3 65.1 57.2 45.4 35.6 34.8 34.5

[0153] As shown in Table 2, the surface tension of the polymer aqueous solutions prepared from the polymers obtained in Examples 1-15 gradually decreased with increasing polymer aqueous solution concentration. At a concentration of 1500 mg / L, the surface tension of the polymer aqueous solution was between 31.4 and 35.8 N / m, exhibiting good surface activity. The surface tension of the acrylamide polymer aqueous solution designated KYP decreased with increasing concentration, but the decrease was small, and the surface tension was between 60 and 70 mN / m. Comparative Example 1 changed the weight ratio of each monomer, Comparative Example 2 replaced an equal weight of acrylamide with acrylic acid, and Comparative Example 3 reduced the amount of polyoxyethylene. Compared with Examples 1-15, the surface tension of the polymer aqueous solution prepared from the polymer obtained in Comparative Example 1 decreased significantly with increasing concentration, indicating poor surface activity. Compared with Examples 1-15, the surface activity of the polymer aqueous solutions prepared from the polymers obtained in Comparative Examples 2 and 3 was better, but the apparent viscosity of the polymer aqueous solution at temperatures of 25°C and 80°C and mineralization of 5 g / L, 15 g / L and 25 g / L all decreased significantly, indicating poor temperature and salt resistance.

[0154] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A surface-active polymer, characterized in that, The surface-active polymer comprises: structural unit A as shown in formula (1), structural unit B as shown in formula (2), and structural unit C as shown in formula (3). Where n is an integer from 7 to 20, and M is an alkali metal element; Based on the total weight of the surface-active polymer, the content of structural unit A is 60-89 wt%, the content of structural unit B is 10-30 wt%, and the content of structural unit C is 1-30 wt%.

2. The surface-active polymer according to claim 1, characterized in that, n is 7, 9 or 15; m is an integer from 10 to 14, preferably 12; Preferably, p is an integer between 6 and 10, and more preferably 8; Preferably, the structural unit B is selected from at least one of the structural units shown in formula (7), formula (8), and formula (9), and the structural unit C is selected from the structural unit shown in formula (13). Preferably, based on the total weight of the surface-active polymer, the content of structural unit A is 70-89 wt%, the content of structural unit B is 10-20 wt%, and the content of structural unit C is 1-10 wt%.

3. The surface-active polymer according to claim 2, characterized in that, The surfactant polymer is selected from one of the following polymers: Polymer-1: comprising the structural unit shown in formula (1), the structural unit shown in formula (7), and the structural unit shown in formula (13). Polymer-2: comprises the structural unit shown in formula (1), the structural unit shown in formula (8), and the structural unit shown in formula (13). Polymer-3: contains the structural unit shown in formula (1), the structural unit shown in formula (9) and the structural unit shown in formula (13).

4. The surface-active polymer according to any one of claims 1-3, characterized in that, The surface-active polymer has a viscosity-average molecular weight of 10 million g / mol to 15 million g / mol, preferably 11 million g / mol to 15 million g / mol.

5. The surface-active polymer according to any one of claims 1-4, characterized in that, The intrinsic viscosity η of the surface-active polymer is 1900-2600 mL / g, and / or the surface tension of a solution of the surface-active polymer at a concentration of 1500 mg / L at 25°C is 31-40 mN / m. Preferably, the intrinsic viscosity η of the surfactant is 2050-2600 mL / g, and / or the surface tension of a solution of the surfactant at a concentration of 1500 mg / L is 31.5-35.6 mN / m at 25°C.

6. A method for preparing a surface-active polymer, characterized in that, The preparation method includes: polymerizing a monomer mixture in water in the presence of an initiator, wherein the monomer mixture contains monomer D as shown in formula (4), monomer E as shown in formula (5), and monomer F as shown in formula (6). Where n is an integer between 7 and 20, and M is an alkali metal element; Based on the total weight of the monomer mixture, the amount of monomer D added is 60-89 wt%, the amount of monomer E added is 10-30 wt%, and the amount of monomer F added is 1-30 wt%. Preferably, based on the total weight of the monomer mixture, the amount of monomer D added is 70-89 wt%, the amount of monomer E added is 10-20 wt%, and the amount of monomer F added is 1-10 wt%.

7. The preparation method according to claim 6, characterized in that, n is 7, 9 or 15; m is an integer from 10 to 14, preferably 12; Preferably, p is an integer between 6 and 10, and more preferably 8; Preferably, the monomer E is selected from at least one of the monomers shown in formula (10), formula (11), and formula (12), and the monomer F is selected from the monomer shown in formula (14). Preferably, the amount of the monomer mixture added is 15-35 wt%, more preferably 20-30 wt%, based on the total weight of water and the monomer mixture.

8. The preparation method according to claim 6 or 7, characterized in that, The polymerization reaction is carried out at a temperature of 0-25℃, preferably 0-15℃, for a time of 2-15h, preferably 10-15h. Preferably, the polymerization reaction is carried out at a pH of 7-10, and more preferably at a pH of 7-9; Preferably, the polymerization reaction is carried out in the presence of a protective gas, which is selected from at least one of nitrogen and group 0 elements in the periodic table; Preferably, the protective gas is selected from nitrogen and / or argon.

9. The preparation method according to any one of claims 6-8, characterized in that, Based on the total weight of the monomer mixture, the amount of initiator added is 0.01-0.1 wt%. Preferably, the initiator is selected from at least one of azo initiators, peroxide initiators, and redox initiators.

10. The preparation method according to any one of claims 6-9, characterized in that, The polymerization reaction is carried out in the presence of a chelating agent; Preferably, the amount of chelating agent added is 0.1-0.3 wt%, based on the total weight of the monomer mixture; Preferably, the chelating agent is selected from at least one of disodium ethylenediaminetetraacetate, aminotriacetic acid, and ammonium citrate, and is more preferably disodium ethylenediaminetetraacetate; Preferably, the polymerization reaction is carried out in the presence of an auxiliary agent; Preferably, the amount of the additive added is 0.01-0.1 wt%, based on the total weight of the monomer mixture; Preferably, the adjuvant is selected from at least one of urea, thiourea and ammonia water, and preferably urea; Preferably, the polymerization reaction is carried out in the presence of a molecular weight regulator; Preferably, the amount of the molecular weight regulator added is 0.02-0.1 wt%, based on the total weight of the monomer mixture; Preferably, the molecular weight regulator is selected from at least one of isopropanol, ammonia, N,N'-methylenebisacrylamide and dimethylthiourea, and is more preferably a mixture of isopropanol and ammonia; Preferably, the weight ratio of isopropanol to ammonia in the molecular weight regulator is (15-35):

1.

11. A surface-active polymer prepared by the preparation method according to any one of claims 6-10.

12. The use of the surfactant polymer according to any one of claims 1-5, 11 as a polymeric oil displacement agent.

Citation Information

Patent Citations

  • Modified PVA polyvinyl alcohol polymer surfactant for displacement of reservoir oil

    CN105331347A